PELAKSANAAN IN HOUSE TRAINNING (IHT) PEMBUATAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) SATU LEMBAR UNTUK MENINGKATKAN KOMPETENSI GURU DI SMP - Abuzar Gafari (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study departs from the results of the quality report cards for SMP Negeri 4 Muara Bungo and the results of observations in the classrooms, it is concluded that most teachers have not made RPP optimally in accordance with national standards. In House Training Activities are one of the self-development activities carried out in schools, namely the RPP Component according to the Regulation of the Minister of Education and Culture Number 22 of 2016 concerning the Standards for the Primary and Secondary Education Process consisting of 13 RPP Components and the Making of 1 Sheet RPP in accordance with the Circular of the Minister of Education and Culture No. 14 of 2019 concerning the making of one-sheet RPP, which is still guided by the 2013 Curriculum RPP. In this IHT Activity, the achievement of making RPP with 13 assessment components from cycle 1 to cycle 2 has increased. In cycle one, the average attainment of participants' attitudes was 82.7% (good) while in cycle 2 it was 88.09% (very good). The achievement of making lesson plans in cycle 1 is 84.74% (Good) while Cycle 2 is worth 93.7 (very good). This increase shows that the implementation of IHT can improve teacher competence both from the achievement of activities/attitudes and the achievement of competence in making lesson plans. Of the thirteen good RPP components based on Curriculum 13 according to the Regulation of the Minister of Education and Culture Number 22 of 2016 and the Circular Letter of the Minister of Education and Culture No. 14 of 2019 concerning the Making of one-sheet RPP Cycle one and cycle two, the lowest is the Making of one-sheet RPP, namely 1. Suitability of Learning Objectives, 2. Learning Media, 3. Learning Steps and 4. Learning Assessment. This is because these four components require broad insight and knowledge, and are in accordance with class/student conditions.